Workshop Pemahaman Administrasi Gudang untuk Generasi Milenial - Siti Aisyah; Virgo Simamora (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
Warehousing is an important part of the supply chain, which functions as a place to store goods before being distributed to consumers or customers. An understanding of warehouse administration plays a vitally important role in the supply chain of various business aspects. Warehouse administration which involves management processes such as planning, monitoring and organizing warehouses is carried out to help companies reduce costs and increase profits. This includes stock management, inventory control, shipping, receiving, and data management. Warehouse administration aims to ensure the warehouse runs efficiently and effectively. In this community service activity, an understanding of warehouse administration is provided using community service methods in the form of outreach. Participated by 24 people from the millennial generation, this socialization carried the theme "Understanding of Warehouse Administration for the Millennial Generation" and had discussion points regarding the role of warehouse administration tasks, the scope of warehouse administration. The aim of holding this socialization is that it is hoped that the millennial generation can gain a better understanding of warehouse administration and can also provide significant benefits for the millennial generation, both in developing personal skills and preparing for future careers.